Marketing 4.0 : moving from traditional to digital - Kotler, Philip 1931- (John Wiley & Sons, 2017)
Marketing 4.0: Moving from Traditional to Digital is the much-needed handbook for next-generation marketing. Written by the world's leading marketing authorities, this book helps you navigate the increasingly connected world and changing consumer landscape to reach more customers, more effectively. Today's customers have less time and attention to devote to your brand?and they are surrounded by alternatives every step of the way. You need to stand up, get their attention, and deliver the message they want to hear. This book examines the marketplace's shifting power dynamics, the paradoxes wrought by connectivity, and the increasing sub-culture splintering that will shape tomorrow's consumer; this foundation shows why Marketing 4.0 is becoming imperative for productivity, and this book shows you how to apply it to your brand today.